Overview of Biologically Active Nucleoside Phosphonates - Groaz, Elisabetta; De Jonghe, Steven (Frontiers in Chemistry, 2021)
The use of the phosphonate motif featuring a carbon-phosphorous bond as bioisosteric replacement of the labile P-O bond is widely recognized as an attractive structural concept in different areas of medicinal chemistry, since it addresses the very fundamental principles of enzymatic stability and minimized metabolic activation. This review discusses the most influential successes in drug design with special emphasis on nucleoside phosphonates and their prodrugs as antiviral and cancer treatment agents. A description of structurally related analogues able to interfere with the transmission of other infectious diseases caused by pathogens like bacteria and parasites will then follow. Finally, molecules acting as agonists/antagonists of P2X and P2Y receptors along with nucleotidase inhibitors will also be covered. This review aims to guide readers through the fundamentals of nucleoside phosphonate therapeutics in order to inspire the future design of molecules to target infections that are refractory to currently available therapeutic options.